An Introduction to Radiative Transfer: Methods and Applications in Astrophysics. - Peraiah, Annamaneni (Cambridge University, 2013)
Astrophysicists have developed several very different methodologies for solving the radiative transfer equation. An Introduction to Radiative Transfer presents these techniques as applied to stellar atmospheres, planetary nebulae, and other objects with similar geometrical and physical conditions.